Effect of particle size on oral absorption of carvedilol nanosuspensions: in vitro and in vivo evaluation - Liu DD (Dove Medical Press, 2015)
Dandan Liu,1 Hao Pan,2 Fengwei He,1 Xiaoyu Wang,3 Jinyu Li,3 Xinggang Yang,3 Weisan Pan31Department of Pharmaceutical Engineering, School of Biomedical and Chemical Engineering, Liaoning Institute of Science and Technology, Benxi, People’s Republic of China; 2School of Pharmacy, Queen’s University Belfast, Belfast, Northern Ireland, UK; 3Department of Pharmaceutics, School of Pharmacy, Shenyang Pharmaceutical University, Shenyang, People’s Republic of China Abstract: The purpose of this work was to explore the particle size reduction effect of carvedilol on dissolution and absorption. Three suspensions containing different sized particles were prepared by antisolvent precipitation method or in combination with an ultrasonication process. The suspensions were characterized for particle size, surface morphology, and crystalline state. The crystalline form of carvedilol was changed into amorphous form after antisolvent precipitation. The dissolution rate of carvedilol was significantly accelerated by a reduction in particle size. The intestinal absorption of carvedilol nanosuspensions was greatly improved in comparison with microsuspensions and solution in the in situ single-pass perfusion experiment. The in vivo evaluation demonstrated that carvedilol nanosuspensions and microsuspensions exhibited markedly increased Cmax (2.09- and 1.48-fold) and AUC0–t (2.11- and 1.51-fold), and decreased Tmax (0.34- and 0.48-fold) in contrast with carvedilol coarse suspensions. Moreover, carvedilol nanosuspensions showed good biocompatibility with the rat gastric mucosa in in vivo gastrointestinal irritation test. The entire results implicated that the dissolution rate and the oral absorption of carvedilol were significantly affected by the particle size. Particle size reduction to form nanosized particles was found to be an efficient method for improving the oral bioavailability of carvedilol. Keywords: carvedilol, nanosuspensions, intestinal absorption, oral bioavailability, gastrointestinal irritation